The issue of balance training in cross-country skiing - Nosek, M.; Mullerová, B. (Journal of Outdoor Activities, 2015)
The basis of correct and efficient implementation of techniques in cross-country skiing is balance. In our article, we focus on the description of balance capabilities and its role in cross-country skiing. We describe the possibility of using modern tools and utensils for its development. We also recommend a methodological procedure to develop balance both in the summer months which we call "Dry" training, also in the winter snow. Part of the text are also suggestions of exercises and selected exercises suitable for developing balance and individual key skills for school conditions which can rehearse during Physical Education classes before the ski course.